Cost and benefit analysis for climate-smart soil practices in Western Kenya. - Karanja Ng'ang'a, Stanley; Notenbaert, An Maria Omer; Mwungu, Chris Miyinzi; Mwongera, Caroline; Girvetz, Evan Hartunian (2017)
Most of the countries in sub-Saharan Africa (SSA), including Kenya, depend heavily on agriculture for income and food security. Any effort aiming to sustain and improve the productivity in agriculture is, therefore, an important step towards improving the livelihoods of many households. Soils are integral to the function of food and fibre production. In addition, they have a large potential for sequestering carbon and mitigating greenhouse gases. The adoption of climate-smart soil practices can improve the soil-nitrogen cycle, enhance yield, soil fertility, crop productivity, improve soil biodiversity, and reduce soil erosion and water pollution. This could, in turn, help to boost food production, income and household ability to adapt. However, a review of published literature indicates a lack of in-depth empirical analysis on the costs and benefits associated with implementing these climate-smart soil (CSS) practices. Therefore, there is a gap about the cost effectiveness of adopting these practices – a key ingredient to the development of appropriate policies. The results presented in this paper attempt to bridge this knowledge gap, using an ex-ante cost and benefit analysis (CBA) to assess the cost-effectiveness of a few selected CSS practices in three counties in Western Kenya. The study’s main goal is to assess costs and benefits of selected CSS practices as a step toward understanding whether it is beneficial or not – both from private and social points of view – for farmers who have implemented them.